2020
DOI: 10.1126/sciadv.aay0114
|View full text |Cite
|
Sign up to set email alerts
|

Correlation-driven eightfold magnetic anisotropy in a two-dimensional oxide monolayer

Abstract: Engineering magnetic anisotropy in two-dimensional systems has enormous scientific and technological implications. The uniaxial anisotropy universally exhibited by two-dimensional magnets has only two stable spin directions, demanding 180° spin switching between states. We demonstrate a previously unobserved eightfold anisotropy in magnetic SrRuO3 monolayers by inducing a spin reorientation in (SrRuO3)1/(SrTiO3)N superlattices, in which the magnetic easy axis of Ru spins is transformed from uniaxial 〈001〉 dire… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 52 publications
(53 reference statements)
0
48
0
1
Order By: Relevance
“…Particularly, a SrRuO3/SrTiO3 superlattice (SRO/STO SL) is an ideal prototype for selectively controlling the crystalline symmetry and magnetic anisotropy of SRO. [28][29][30] In this study, we demonstrate the customization of the spin-wave gap in SRO through artificial crystalline symmetry control. We fabricated SRO/STO SLs using pulsed laser epitaxy with atomic-scale precision.…”
Section: Introductionmentioning
confidence: 91%
“…Particularly, a SrRuO3/SrTiO3 superlattice (SRO/STO SL) is an ideal prototype for selectively controlling the crystalline symmetry and magnetic anisotropy of SRO. [28][29][30] In this study, we demonstrate the customization of the spin-wave gap in SRO through artificial crystalline symmetry control. We fabricated SRO/STO SLs using pulsed laser epitaxy with atomic-scale precision.…”
Section: Introductionmentioning
confidence: 91%
“…Transition metal oxide SrRuO 3 provides an ideal platform to investigate Berry curvature, because it is a 4d metallic ferromagnet with a sizable SOC (17)(18)(19)(20), in which the AHE mainly arises from the Berry curvature of its electronic band structure (11,21,22). Due to the strong coupling between lattice distortions and electronic structure in transition metal oxides, previous studies have already revealed that epitaxial strain has profound effects on magnetic properties of SrRuO 3 films (23)(24)(25)(26)(27)(28)(29)(30)(31)(32). These results suggest that epitaxial strain might be an effective approach to manipulating Berry curvature and related AHE in SrRuO 3 thin films, which, however, has not been comprehensively investigated yet.…”
mentioning
confidence: 99%
“…To get a quantitative description of the PMA strength, the effective anisotropy constant (K eff ) was quantitatively estimated by the shadow area between the OOP and IP magnetization curves as shown Fig. S8 [43]. The negative and positive values of K eff refer to the IP and OOP magnetic anisotropy, respectively.…”
Section: Thickness Dependence Of the Electric Transport Anisotropy In...mentioning
confidence: 99%